Feasibility of Using Commercially Available Accelerometers to Monitor Upper Extremity Home Practice With Persons Post-stroke: A Secondary Data Analysis - de Castro, Kate N.; Donoso Brown, Elena V.; Miller Neilan, Rachael; Wallace, Sarah E. (Frontiers in Virtual Reality, 2021)
Background: Adherence to home practice rehabilitation programs is important for efficacy; however, adherence is challenging for many individuals post-stroke. Accelerometers have emerged as a potential means to support home practice. This secondary data analysis explored the use of a commercially available accelerometer with custom software to collect and analyze data to corroborate self-reported practice collected during a home program. Methods: The initial study was a single subject design trial that investigated the effect of preferred music listening on adherence to an upper extremity home practice program (Trial Number NCT02906956. ClinicalTrial.gov). The participants (n=7) were post-stroke adults with aphasia and hemiparesis of the upper extremity. Participants completed home program exercises while wearing accelerometers and recorded practice times in a logbook. Data were collected, cleaned, processed, and analyzed to facilitate descriptive comparisons and clinical interpretations of accelerometer output data. Results: Across all participants, an average of 47% of data were captured and usable for analysis. Six out of seven participants self-reported longer practice times compared to accelerometer duration output by a mean of 49.37 seconds. Individual set mean total angular velocity and standard deviation of acceleration demonstrated potential for use across time to monitor change. Conclusions: One challenge of integrating accelerometers into clinical practice is the amount of data loss and the steps to data processing. The comparisons of available accelerometer data to the self-reported logs, however, were generally representative. Future investigations should explore ways to increase data capture and accessibility of the data for feedback to the client and practitioner.